Cystatin C-Based Renal Function in Predicting the Long-Term Outcomes of Chronic Total Occlusion After Percutaneous Coronary Intervention - Li, Bolin; Rong, Jie; Wang, Bobo; Gao, Ke; Wen, Xing; Li, Hongbing; Cheng, Lele; Hua, Yi-Ming; Li, Shanshan; Jian, Zhijie; Zhang, Yujing; Huang, Hui; et al. (Frontiers in Cardiovascular Medicine, 2020)
Renal function estimated by various biomarkers predicting for adverse cardiovascular events has not been well identified in received percutaneous coronary intervention (PCI) for chronic total occlusion (CTO), the advanced stages of atherosclerosis. We aim to determine whether the serum cystatin C-based-estimated glomerular filtration rate (eGFR) can have an improved predictive value in patients with CTO lesions undergoing PCI as compared with multiple creatinine-based estimates of kidney function. Six hundred and seventy-one patients received CTO PCI were retrospectively included in the study. The eGFR was calculated by modification of diet in renal disease equation for Chinese (cMDRD) and Chronic Kidney Disease Epidemiology Collaboration (CKD-EPI) equations at baseline, respectively. And then the cohort was categorized into three groups according to standard KDIGO kidney stages based on eGFR. The primary endpoint was all-cause mortality and the secondary endpoint was cardiac death. Strikingly, cystatin C-based eGFR showed a better performance with the greater area being under the receiver operating characteristic (ROC) curve (0.73 for all-cause mortality and 0.73 for cardiac death, separately) and a better assessment for survival free from adverse event across renal levels among four eGFR equations. Compared with eGFR calculated by other formulas, serum cystatin C -based eGFR showed the highest prognostic value for both all-cause mortality (adjusted HR 3.6, 95%CI 1.6-8.1, P = 0.002) and cardiac death (adjusted HR 2.9, 95%CI 1.0-8.1, P = 0.028). Moreover, cystatin C-based eGFR significantly improved the risk reclassification of event with a high value of net reclassification improvement and integrated discrimination improvement. This study may prove that cystatin C-based eGFR is a better predictor of both all-cause mortality and cardiac death than other equations in populations with CTO undergoing PCI.